Mitochondrial DNA‐depleter mouse as a model to study human pigmentary skin disorders. (4th September 2020) - Villavicencio, Kyrene M.; Ahmed, Noha; Harris, Melissa L.; Singh, Keshav K.
Abstract: Pigmentation abnormalities are reported in the spectrum of phenotypes associated with aging and in patients with mitochondrial DNA depletion syndrome (MDS). Yet, a relevant animal model that mimics these effects and would allow us to evaluate the detrimental aspects of mtDNA depletion on melanocyte function has not been described. Here, we characterize the pigmentary changes observed in the ears of a mtDNA‐depleter mouse, which phenotypically includes accentuation of the peri‐adnexal pseudonetwork, patchy hyper‐ and hypopigmentation, and reticular pigmentation. Histologically, these mice show increased epidermal pigmentation with patchy distribution, along with increased and highly dendritic melanocytes. These mtDNA‐depleter mice mimic aspects of the cutaneous, pigmentary changes observed in humans with age‐related senile lentigines as well as MDS. We suggest that this mouse model can serve as a novel resource for future interrogations of how mitochondrial dysfunction contributes to pigmentary skin disorders. The mtDNA‐depleter mouse model also serves as a useful tool to identify novel agents capable of treating pigmentary changes associated with age‐related mitochondrial dysfunction in humans.